Intraparotid facial nerve schwannoma: a case report - Md Nor, Azmi; Awang, Ahmad Khadri; Raja Lope Ahmad, Raja Ahmad Al'konee (Faculty of Medicine, International Islamic University Malaysia, 2006)
Neoplasms of the facial nerve presenting as a parotid mass are uncommon. In the absence of a facial palsy, preoperative diagnosis of parotid tumour as schwannoma is very difficult1. A rare case of solitary schwannoma involving the branches of the facial nerve